Periodismo del siglo XXI, evolución, alcances y nuevos retos. - Velasco Zurita, Mauricio Javier (2016)
This paper will discuss about new formats and related tools to journalism and how technology has transformed the flow of information allowing citizens/people to engage the media agenda through social networking. This study also allows to delimit the best way of improve the inherent topics in professional changes and in the daily practice in the journalism to stablish the preference at the moment to inform, if is better in paper or web. Carcelén sector was taken as the workspace where surveys and interviews were conducted with the population and an expert on the matter. Also it was a reference “El Comercio” daily content on paper and web to show the information management in both areas. The first phase of study occurred between December 5, 2015 and April 15, 2016. I invite you to keep reading this study to understand the obtained results and in order to understand the references when people search information and the most used tools at the present time and how journalism has evolved.